Legal Regime of the Transfer of Securities on the Radio Spectrum: The Secondary Market - Soto Carrillo, Gerardo (2015)
This paper describes the regulation of radio spectrum transfer for public telecommunications services, as part of the secondary market for spectrum. The legal framework and administrative precedents issued by competent authorities are analyzed.